Técnicas de comunicación asertiva para prevenir el consumo de alcohol de los estudiantes de segundo año de bachillerato de la unidad educativa “Fernando Suarez Palacio” del barrio Carigan de la ciudad de Loja periodo 2013 - 2014 - Jiménez Vega, Cristina Anabel (2015)
This research aims to implement assertive communication techniques to prevent the consumption of alcohol by students of sophomore year. Study descriptive, cross- sectional and quasi -experimental design; methods: descriptive, analytic-synthetic, inductive -deductive, historical and logical, comprehensive, scientific diagnostic model and valuation. A survey and Scale adolescent involvement with alcohol, applied in a sample of 24 students was used. Results: diagnosis, 83.33% of students consumed alcohol; the pretest is that 45.83 % maintained a moderate alcohol use and abuse 25.00% of consumption. After the intervention decreased to moderate use and abuse 41.67 % to 20 % (postest). The r (x, y) is equal to 0.98. It is concluded that the highest percentage of those investigated in the family consume alcohol starting at early ages and with friends. The psychoeducational proposal is valid, then reaches a very high positive correlation.